Txo species of acaricis (Acari: Tenuipalpidae) from Nex Zealand, moved from the genus Tenuipalpus, xith a key to the knoxn species - Castro, Elizeu B. [UNESP]; Beard, Jennifer J.; Ronald, Ochoa; Feres, Reinaldo J. F. [UNESP] (Les Amis d'Acarologia, 2018)
Acaricis Beard & Gerson (Acari: Tenuipalpidae) is a small genus of flat mites with three species described from Australian and New Zealand sedges (Poales: Cyperaceae). In this article, we redescribe two species, Tenuipalpus montanus Collyer and T. alpinus Collyer, and move them to the genus Acaricis, so that these species become Acaricis montanus (Collyer) comb. nov. and A. alpinus (Collyer) comb. nov.. These two species share several characters with other Acaricis that species of Tenuipalpus do not. A key to the world species of Acaricis is also proposed.
Keywords: Acaricis alpinus; Acaricis montanus; False spider mites; Flat mites; Taxonomy